Analysis of bachelor students’ perspectives from the pedagogical department on academic challenges in school education - Aryanti; Ghany Taufik Sidik; Rianita Puspitasari (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
Elementary school education in Indonesia faces academic challenges, including curriculum changes, uneven teacher competence, limited facilities, and low student motivation, which affect learning effectiveness. Previous studies have mainly examined these issues from teachers or policymakers, while limited research explores the views of bachelor’s students from the pedagogical department enrolled in the primary school teacher education program as prospective elementary school teachers. This study addresses this gap by analyzing their perspectives on academic challenges in Indonesian elementary schools. This study used a qualitative approach involving 22 undergraduate students from the pedagogical department in the primary school teacher education program at a public university in Bandung, Indonesia, selected through purposive sampling. Data were collected through in-depth interviews and analyzed using thematic analysis. The findings reveal five main challenges: curriculum changes and relevance, teacher competence and availability, teaching and learning implementation issues, student potential and learning attitudes, and limitations in educational facilities and infrastructure. These results indicate that academic challenges in elementary school education are multidimensional and related to human resource capacity and policy implementation. The study provides insights for developing adaptive and inclusive policies to improve elementary school learning in Indonesia.